1972
DOI: 10.1017/s0021859600087761
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary deficiencies of energy, protein and calcium on the pregnant ewe. I. Body composition and mineral content of the ewes

Abstract: SUMMARYForty 6½-year-old Scottish Blackface ewes were used in an experiment to investigate the effects of low protein and low calcium (Ca) intakes during pregnancy on body composition and mineral contents. Six sheep were slaughtered at the commencement of the experiment as controls; 28 were used in a 2 × 2 factorial experiment in which semipurified diets containing 11·8 and 6·0% crude protein (CP) and 1·2 and 0·11% Ca in the dry matter were offered to maintain non-esterified fatty acids (NEFA) and ketone bodie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
2
1

Year Published

1974
1974
1995
1995

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 23 publications
3
33
2
1
Order By: Relevance
“…Cette caractéristique a été reliée à l'antagonisme existant entre néoglucogenèse et lipogenèse. Il faut toutefois remarquer que la lipogenèse de novo hépatique est également faible chez certaines espèces monogastriques telles que le porc (O'Hea et Leveillé, 1969 ;Mersmann et al, 1973) Heaney, 1973a ;Rattray et al, 1974a ;Heaney et Lodge, 1975) mais l'inverse a pu être observé (Foot, 1969) ; les brebis portant 3 ou 4 fcetus perdent plus de lipides (ou en déposent moins) que celles qui n'en portent qu'un ou deux (Robinson et a/., 1978 ;Purroy Unanua et al, 1978) ; celles qui reçoivent une alimentation libé-rale peuvent soit mobiliser, soit déposer des lipides pendant le dernier tiers de la gestation (Wallace, 1948c ;Foot, 1969 ; Tissier et al, 1980a, b) ; les quelques résultats concernant la première moitié de la gestation sont contradictoires ; des brebis sous-alimentées peuvent mobiliser plus de 50 % de leurs réserves lipidiques pendant la gestation IField et al, 1968 ;Russel et al, 1968 ; Field, 1972 ;Robinson et al, 1978b ;Rattray et al, 1980 ;Geenty et Sykes, 1986).…”
Section: Préambuleunclassified
“…Cette caractéristique a été reliée à l'antagonisme existant entre néoglucogenèse et lipogenèse. Il faut toutefois remarquer que la lipogenèse de novo hépatique est également faible chez certaines espèces monogastriques telles que le porc (O'Hea et Leveillé, 1969 ;Mersmann et al, 1973) Heaney, 1973a ;Rattray et al, 1974a ;Heaney et Lodge, 1975) mais l'inverse a pu être observé (Foot, 1969) ; les brebis portant 3 ou 4 fcetus perdent plus de lipides (ou en déposent moins) que celles qui n'en portent qu'un ou deux (Robinson et a/., 1978 ;Purroy Unanua et al, 1978) ; celles qui reçoivent une alimentation libé-rale peuvent soit mobiliser, soit déposer des lipides pendant le dernier tiers de la gestation (Wallace, 1948c ;Foot, 1969 ; Tissier et al, 1980a, b) ; les quelques résultats concernant la première moitié de la gestation sont contradictoires ; des brebis sous-alimentées peuvent mobiliser plus de 50 % de leurs réserves lipidiques pendant la gestation IField et al, 1968 ;Russel et al, 1968 ; Field, 1972 ;Robinson et al, 1978b ;Rattray et al, 1980 ;Geenty et Sykes, 1986).…”
Section: Préambuleunclassified
“…Dietary protein has been reported to have no effect on Ca absorption in dairy cattle (210), but Ca retention is decreased in pregnant sheep given a low protein diet (191). Sykes & Field (191) suggested that an inadequate protein intake might result in impaired formation of bone matrix and a consequent decrease in accretion of Ca into bone.…”
Section: Dietary Factors Affecting the Availability Of Calcium And Phmentioning
confidence: 99%
“…These 2 factors can be involved in variations of GIT weight so that their respective effects must be disconnected. The dietary protein content of the diet, at similar dry matter (DM) intake, did not modify the weight of GIT in trials by Sykes and Field (1972) (Grimaud and Doreau, 1995). Rompala et al (1990) observed that bulk caused an increase in Na + , K + -ATPase activity, which could enhance glucose absorption.…”
Section: Introductionmentioning
confidence: 99%